Molecular identification of coffee (Coffea arabica) pollinator insects in North Sumatra, Indonesia based on designed COI primers - AIDA FITRIANI SITOMPUL; ELIDA HAFNI SIREGAR; DEWI IMELDA ROESMA; DAHELMI DAHELMI; EKO PRASETYA (Society for Indonesian Biodiversity, 2018)
Sitompul FA, Siregar EH, Roesma DI, Dahelmi, Prasetya E. 2018. Molecular identification of coffee (Coffea arabica) pollinator insects in North Sumatra, Indonesia based on designed COI primers. Biodiversitas 19: 1877-1883. Coffee (Coffea arabica L.) is one of the most important economic commodities in the province of North Sumatra, Indonesia. Insects associated with pollination of C. arabica are one of the key factors for successful cultivation of C. arabica, but, the research regarding of these was still limited. The population of coffee plant is scattered across the highlands of Indonesia and the pollination of C. arabica is strongly believed linked to a diverse group of pollinating insects. However, lack of taxonomic identification of insects pollinating these plants has become one of constraints to succeed the cultivation of C. Arabica. This study aimed to analyze types and variations of pollinating insects of C. arabica in the province of North Sumatra, Indonesia, using DNA barcoding. DNA barcoding is now considered an alternative method of molecular identification. Sixteen of C. arabica flower visitors were captured in different planting location in North Sumatra province. Using mtDNA markers, the cytochrome oxidase subunit sequence I (COI), about 12 pollinator insect species were identified based on the COI sequence i.e Amegilla cingulata, Apis dorsata, Apis cerana, Trigona chanchamayoensis, Idiella divisa, Dolichopodidae sp., Allactoneura sp., Stomorhina discolor, Phytomia erratica, Rhiniidae sp., Melipona bicolor, and Hymenoptera sp.